2016
DOI: 10.17265/2161-6264/2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Anatomical Changes in Roots of Chickpea (Cicer arietinum L.) under Drought Stress Condition

Abstract: Chickpea (Cicer arietinum L.) is a crop cultivated in semi-arid and rainfed areas of Pakistan and it experiences terminal drought stress. In this paper, the morpho-anatomical study regarding roots of chickpea was carried out to investigate the drought adaptation strategies. Twelve cultivars of chickpea were grown in pots under drought stress of 70% and 35% field capacity in addition to control (100%). Root segments of mature chickpea plants were sectioned in 2 cm from root-shoot junction and used for making tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Early or speeded up senescence can influence yield in chickpea and can be correlated to high temperatures which is than further emphasized by limiting water availability. Dropping the level of soil moisture below 50% of field capacity excretes drought stress to chickpea (Saeed et al, 2016), which in our study demonstrated with high impact on plant senescence, early onset of flowering in some accessions and very small rate of pod filling.…”
Section: Response Of Chickpea Plants To Water Deficit Under Heat Stressmentioning
confidence: 54%
“…Early or speeded up senescence can influence yield in chickpea and can be correlated to high temperatures which is than further emphasized by limiting water availability. Dropping the level of soil moisture below 50% of field capacity excretes drought stress to chickpea (Saeed et al, 2016), which in our study demonstrated with high impact on plant senescence, early onset of flowering in some accessions and very small rate of pod filling.…”
Section: Response Of Chickpea Plants To Water Deficit Under Heat Stressmentioning
confidence: 54%